Graphitized carbon material as well as preparation method and application thereof

By using transition metal-assisted carbon materials (HGCs) prepared by transition metal assisted in magnetic solid-phase extraction (MSPE), the problem of insufficient adsorption capacity of existing magnetic composite materials in oil samples is solved, and efficient adsorption and sensitive detection are achieved, which is suitable for quantitative analysis of AFB1 in complex vegetable oil matrix.

CN119774600AActive Publication Date: 2025-04-08JIANGXI AGRICULTURAL UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510273791.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The efficiency and reusability of existing magnetic composite materials in magnetic solid phase extraction (MSPE) are limited, especially when dealing with oil samples with high fatty acid content and non-polar environments, the adsorption capacity is insufficient and the anti-interference ability is poor.

Method used

Through the transition metal-assisted carbonization process, a graphitized carbon material (HGC) was prepared. D-(+)-xylose was used as a carbon source, combined with transition metal salts such as iron, cobalt, and nickel, and prepared by high-temperature calcination to form FeO/Fe3O4/HGC material with excellent adsorption properties.

Benefits of technology

FeO/Fe3O4/HGC materials significantly improved the adsorption capacity of aflatoxin B1 (AFB1), with an adsorption capacity of 1179.99 μg·g-1, which is significantly higher than that of traditional carbon materials. Combined with high-performance liquid chromatography-fluorescence detection, AFB1 quantitative analysis with detection limit as low as 2.0 pg·g-1 was achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774600A_ABST
    Figure CN119774600A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material application, and particularly relates to a graphitized carbon material and a preparation method and application thereof.The preparation method of the graphitized carbon material comprises the steps that 1, D-(+)-xylose powder and transition metal salt powder are weighed and fully ground to be uniform; (2) after sieving, calcining in an inert gas atmosphere; and (3) grinding and sieving the calcined product, washing with 1.0 mol / L diluted hydrochloric acid solution, washing with distilled water, and drying to obtain the graphitized carbon material, efficiently adsorbing the aflatoxin B1 (AFB1) in the vegetable oil, combining magnetic solid phase extraction (MSPE) and high performance liquid chromatography-fluorescence detection (HPLC-FLD) technologies, reducing the detection limit to 2.0 pg.g <-1 >, and ensuring that the graphitized carbon material has excellent regeneration performance. And the material consumption and the cost in the detection process are obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material application, and specifically relates to a graphitized carbon material and a preparation method and application thereof. Background Art

[0002] Aflatoxins (AFs) are a class of potent carcinogenic mycotoxins produced by Aspergillus flavus and Aspergillus parasiticus, which often contaminate crops such as soybean, peanut and sesame. The risk of crop oil contamination by AFs is gradually increasing due to insufficient preventive measures during the cultivation and storage of crops, as well as adverse climatic conditions such as high humidity and excessive rainfall. Therefore, it is of great significance to develop sensitive methods for the detection of aflatoxins in crop oils. However, unlike aqueous matrices, the detection of AFs in crop oils faces complex sample preparation challenges due to their high fatty acid content and non-polar environment.

[0003] Magnetic solid phase extraction (MSPE) is a pretreatment technology for oil-based samples. It achieves efficient phase separation through an external magnetic field and has significant advantages over traditional solid phase extraction (SPE) in processing high-viscosity oil samples. However, the efficiency and reusability of existing magnetic composite materials in MSPE are restricted, such as insufficient adsorption capacity and poor anti-interference. Therefore, the development of adsorption materials with high adsorption capacity and excellent regeneration performance to improve the detection efficiency of AFs in oil samples has become a key issue that needs to be solved urgently.

[0004] Carbon materials have shown great application potential in environmental treatment, energy storage and advanced electronic devices due to their high electrical conductivity, excellent chemical stability and unique microstructure. By introducing heteroatoms or composite matrices, the properties of carbon materials can be precisely controlled, giving them high specific surface area, large porosity, adjustable structure and multifunctionality; these properties make carbon materials ideal pollutant adsorbents. However, although carbon materials perform well in aqueous or polar solvent systems, their performance in non-polar environments is still limited, mainly due to the weakening of electrostatic interactions and hydrogen bonding effects. Therefore, it is crucial to develop carbon adsorption materials for non-polar environments. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a graphitized carbon material (HGC). Based on the transition metal-assisted carbonization process strategy, D-(+)-xylose is selected as a carbon source, combined with transition metal salts such as iron, cobalt, and nickel, and high-temperature calcination and other steps to prepare a graphitized carbon material (HGC) with excellent adsorption properties.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a graphitized carbon material comprises the following steps: (1) Weigh D-(+)-xylose powder and transition metal salt powder, and grind them thoroughly into a uniform mixture; (2) After the mixture of step (1) is screened, calcined under an inert gas atmosphere: first at 2°C·min -1 The temperature was heated to 250 °C at a rate of 10 °C min -1 Heat to 750℃~850℃ at a heating rate of , keep constant temperature for 3h~4h, and then cool naturally to room temperature; (3) The magnetic black powder calcined in step (2) is ground and sieved, then washed with a 1.0 mol / L dilute hydrochloric acid solution, then washed with distilled water, and dried to obtain a graphitized carbon material.

[0007] In a preferred example, in step (1), the mass ratio of D-(+)-xylose powder to transition metal salt powder is 4:1.

[0008] In a preferred example, in step (1), the transition metal salt powder is selected from FeCl 3 6H 2 O、CoCl 2 6H 2 O、NiCl 2 6H 2 One of O.

[0009] In a preferred example, in step (1), the transition metal salt powder is selected as FeCl 3 6H 2 O.

[0010] In a preferred example, in step (2), the inert gas is argon.

[0011] Based on a general inventive concept, another object of the present invention is to provide a graphitized carbon material prepared by the above method and its application in detecting aflatoxin B1 in vegetable oil, using the graphitized carbon material FeO / Fe 3 O 4 / HGC uses magnetic solid phase extraction to quantify aflatoxin B1 in vegetable oils and combines it with high performance liquid chromatography-fluorescence detection to obtain a low detection limit of 2.0 pg·g -1 .

[0012] The solid phase extraction (SPE) method of existing carbon materials has advanced application value in the detection of aflatoxin B1 (AFB1) in aqueous food matrices, but it shows significant analytical difficulty in the oil phase with high fatty acid concentration and non-polar environment. The present invention proposes a highly graphitized carbon material (HGC) with enhanced π-π interaction for the extraction of AFB1 in the oil phase through a simple transition metal-assisted carbonization process. The adsorption experiment results show that FeO / Fe 3 O 4 The AFB1 adsorption capacity of / HGC is 1179.99 μg·g -1 , significantly higher than Ni / HGC and Co / HGC (nearly 4 times) and pure carbon materials (nearly 6 times). Density functional theory (DFT) calculations reveal its mechanism, indicating that FeO / Fe 3 O 4 The electron defect properties of the graphitized carbon structure supported by magnetic clusters significantly enhance the π-π interaction with AFB1. In addition, pore filling and hydrophobic interactions also provide complementary effects for the adsorption of AFB1.

[0013] Compared with the prior art, the advantages and positive effects of the present invention are as follows: (1) Highly efficient adsorption performance: Highly graphitized carbon materials (HGC) prepared by transition metal-assisted carbonization process have significantly enhanced π-π interactions, excellent pore filling and hydrophobic interactions, and can achieve efficient adsorption of aflatoxin B1 (AFB1) in complex oil phase matrices. Its adsorption capacity is significantly higher than that of traditional carbon materials. (2) Sensitive detection capability: Magnetic solid phase extraction (MSPE) and high performance liquid chromatography-fluorescence detection (HPLC-FLD) are combined to achieve a detection limit as low as 2.0 pg·g -1 , the recovery rate is between 96.0% and 104.4%, which can meet the sensitivity requirements for trace pollutant detection and is suitable for quantitative analysis of AFB1 in complex vegetable oil matrices; (3) Simple and efficient preparation method: D-(+)-xylose is used as the carbon source and combined with transition metal salts through a simple high-temperature carbonization process. It has the characteristics of easy operation, strong scalability, and environmental friendliness. The prepared carbon material has excellent regeneration performance and significantly reduces the material consumption and cost in the detection process.

[0014] This invention demonstrates for the first time the key role of enhanced π-π chemical bond interactions between molecules in the detection of complex oil matrix pollutants, providing important theoretical and technical support for the development of efficient and sensitive oil matrix pollutant detection technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 for FeO / Fe3 O 4 / SEM image of HGC; Figure 2 In the equation, (a) is FeO / Fe 3 O 4 / HGC, Co / HGC, Ni / HGC and D-Xyl-C adsorption kinetics of AFB1; (b) AFB1 on FeO / Fe 3 O 4 / HGC, Co / HGC, Ni / HGC and D-Xyl-C adsorption isotherm experiments; Figure 3 is the linear relationship between AFB1 concentration and the integrated area of ​​AFB1 chromatographic peak; Figure 4 The curves included are: FeO / Fe 3 O 4 HPLC chromatogram of real rapeseed oil sample by HGC, FeO / Fe 3 O 4 / HGC added 10.0 pg g -1 HPLC chromatogram of rapeseed oil sample of AFB1, FeO / Fe 3 O 4 / HGC added 100.0 pg g -1 HPLC chromatogram of rapeseed oil sample of AFB1, FeO / Fe 3 O 4 / HGC added 250.0 pg g -1 HPLC chromatogram of rapeseed oil sample of AFB1. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in conjunction with specific embodiments, but the present invention is not limited to these embodiments. It should be noted that, under the premise of not conflicting, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. In the present invention, unless otherwise specified, all parts and percentages are mass units, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, if not otherwise specified, are conventional methods in the art.

[0017] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0018] When the amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether this range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise stated, this range is intended to include its end values ​​and all integers and fractions within this range.

[0019] The present invention provides a method for preparing a graphitized carbon material based on a transition metal-assisted carbonization strategy, comprising the following steps: (1) Weigh D-(+)-xylose powder and transition metal salt powder, and grind them thoroughly into a uniform mixture; (2) After the mixture of step (1) is screened, calcined under an inert gas atmosphere: first at 2°C·min -1 The temperature was heated to 250 °C at a rate of 10 °C·min and kept for 1 h to remove crystal water and adsorbed water. -1 Heat to 750℃~850℃ at a heating rate of , keep constant temperature for 3h~4h, and then cool naturally to room temperature; (3) The magnetic black powder calcined in step (2) is ground and sieved, then washed with a 1.0 mol / L dilute hydrochloric acid solution to remove free metal particles and impurities, then washed with distilled water, and dried to obtain a graphitized carbon material.

[0020] In a preferred example, the mass ratio of D-(+)-xylose powder to transition metal salt powder is 4:1.

[0021] In a preferred example, in step (1), the transition metal salt powder is selected from FeCl 3 6H 2 O、CoCl 2 6H 2 O、NiCl 2 6H 2 One of O.

[0022] In a preferred example, in step (1), the transition metal salt powder is FeCl 3 6H 2 O.

[0023] In a preferred example, in step (2), the inert gas is argon.

[0024] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0025] Example 1

[0026] (1) Weigh 4.0 g D-(+)-xylose powder and 1.0 g FeCl 3 6H 2 O powder, in a mortar, grind thoroughly into a homogeneous mixture; (2) After the mixture of step (1) is screened, calcined under an argon atmosphere: first at 2°C·min -1 The temperature was heated to 250 °C at a rate of 10 °C·min and kept for 1 h to remove crystal water and adsorbed water. -1 The sample was heated to 800°C at a heating rate of 100 °C, kept at this temperature for 4 h, and then cooled naturally to room temperature; (3) Grinding and sieving the magnetic black powder calcined in step (2), then washing with 1.0 mol / L dilute hydrochloric acid solution to remove free metal particles and impurities, then washing with distilled water and drying to obtain graphitized carbon material FeO / Fe 3 O 4 / HGC.

[0027] The graphitized carbon material FeO / Fe prepared in Example 1 3 O 4 / HGC morphology characterization, FeO / Fe 3 O 4 The scanning electron microscopy images of / HGC show a quasi-spherical structure with an average diameter of about 5 μm, and its surface is densely covered with metal nanoparticles (e.g. Figure 1 As shown); the transition metal ions with empty d orbitals interact with the lone pair electrons on the oxygen atoms in D-(+)-xylose, promoting the formation of a uniform and thermally stable mixture, which affects the resulting structure and adsorption properties.

[0028] Example 2

[0029] (1) Weigh 4.0 g D-(+)-xylose powder and 1.0 g CoCl 2 6H 2 O powder, in a mortar, grind thoroughly into a homogeneous mixture; (2) After the mixture of step (1) is screened, calcined under an argon atmosphere: first at 2°C·min -1 The temperature was heated to 250 °C at a rate of 10 °C·min and kept for 1 h to remove crystal water and adsorbed water. -1 The sample was heated to 800°C at a heating rate of 100 °C, kept at this temperature for 4 h, and then cooled naturally to room temperature; (3) The magnetic black powder calcined in step (2) is ground and sieved, then washed with a 1.0 mol / L dilute hydrochloric acid solution to remove free metal particles and impurities, then washed with distilled water, and dried to obtain a graphitized carbon material Co / HGC.

[0030] Example 3

[0031] (1) Weigh 4.0 g D-(+)-xylose powder and 1.0 g NiCl 2 6H 2 O powder, in a mortar, grind thoroughly into a homogeneous mixture; (2) After the mixture of step (1) is screened, calcined under an argon atmosphere: first at 2°C·min -1 The temperature was heated to 250 °C at a rate of 10 °C·min and kept for 1 h to remove crystal water and adsorbed water. -1 The sample was heated to 800°C at a heating rate of 100 °C, kept at this temperature for 4 h, and then cooled naturally to room temperature; (3) The magnetic black powder calcined in step (2) is ground and sieved, then washed with a 1.0 mol / L dilute hydrochloric acid solution to remove free metal particles and impurities, then washed with distilled water, and dried to obtain a graphitized carbon material Ni / HGC.

[0032] Feasibility study of detection strategy

[0033] ① 1mg FeO / Fe 3 O 4 / HGC powder dispersed in 10mL 120ng·L −1 AFB1 solution. The samples were subjected to different shaking times ranging from 1 min to 120 min. After shaking, the supernatant was collected using a 0.22 μm filter membrane for HPLC-fluorescence detection; ② 1mg FeO / Fe 3 O 4 / HGC powder was dispersed in 10 mL of different initial concentrations (1 ng·mL -1 ~180 ng·mL -1 ) in AFB1 solution. The solution was shaken at room temperature for 30 min, and the supernatant was collected using a 0.22 μm filter membrane for HPLC-fluorescence detection; ③ Add 4.0mg FeO / Fe 3 O 4 / HGC powder and 20.0 mL of AFB1 solutions of different concentrations were added to a 50.0 mL centrifuge tube. The mixture was shaken for 8 min using a vibrator, and then a magnet was placed at the bottom of the test tube to separate the supernatant. Subsequently, 1.0 mL of DMF solution was added as an eluent, and the mixture was shaken for another 5 min. Under an external magnetic field, the eluent was collected within 1 min. The collected solution was filtered through a 0.22 μm organic phase membrane and then subjected to high performance liquid chromatography-fluorescence detection; The adsorption results of the above test ① are as follows Figure 2 As shown in (a), FeO / Fe 3 O 4 / HGC showed efficient extraction ability and reached adsorption equilibrium within 12min to 15min. 3 O 4 The adsorption of AFB1 by / HGC follows the pseudo-second-order model, indicating that the adsorption process of AFB1 by the material is mainly controlled by chemical adsorption. In addition, the adsorption results of the above experiment ② are as follows Figure 2 As shown in (b), FeO / Fe 3 O 4 The adsorption isotherm of / HGC is in good agreement with the Langmuir model, showing a 1179.99 μg·g -1 The maximum adsorption capacity of FeO / Fe 3 O 4 The high surface area, porous structure and multivalent metal components of HGC contribute to its strong interaction with AFB1 and improve its adsorption performance. Based on experiment ③, the standard curve (such as Figure 3 As shown in Figure 2), the linear detection range and detection limit of the MSPE-HPLC-FLD method for AFB1 established in the present invention were calculated to be 5.0 pg·g -1 ~1000.0 pg g -1 and 2.0 pg g -1 , indicating that this method can indeed achieve high-sensitive detection of AFB1.

[0034] Experiment to prove the reliability of standard curve

[0035] In order to evaluate the feasibility of the MSPE-HPLC-FLD method constructed in the present invention in detecting AFB1 in real samples, the spiked recovery rate of AFB1 in real plant oil samples was studied using this method.

[0036] The preparation method of the spiked samples was as follows: first, rapeseed oil from two different brands was collected and divided into several parts; then, different concentrations of AFB1 were added in sequence, and then filtered to remove insoluble impurities, and the obtained filtrate was used as the spiked sample for subsequent experiments.

[0037] Table 1 Recovery and relative standard deviation of AFB1 (n=6) in spiked samples

[0038] The results are shown in Table 1 above. This method showed good recoveries (96.0% to 104.4%) for spiked samples. 3 O 4 The HPLC chromatogram of the real rapeseed oil-2 sample by HGC is shown in Figure 4 As shown, it is confirmed that the MSPE-HPLC-FLD method constructed in the present invention has good application prospects in the detection of AFB1.

[0039] The present invention adopts FeO / Fe 3 O 4 A highly efficient and sensitive method for the quantitative analysis of trace amounts of AFB1 in vegetable oils was established by combining solid phase extraction of HGC with high performance liquid chromatography-fluorescence detection (HPLC-FLD), with a detection limit as low as 2.0 pg g -1 The recovery rate is 96.0% to 104.4%. The present invention can meet the sensitivity requirements for the detection of trace pollutants, and provides an efficient tool for the detection of AFB1 in vegetable oil, which is of great significance for ensuring food safety.

[0040] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a graphitized carbon material, characterized in that: The following steps are involved: (1) Weigh D-(+)-xylose powder and transition metal salt powder, and grind them thoroughly into a uniform mixture; (2) After the mixture of step (1) is screened, calcined under an inert gas atmosphere: first at 2°C·min -1 The temperature was heated to 250 °C at a rate of 10 °C min -1 Heat to 750℃~850℃ at a heating rate of , keep constant temperature for 3h~4h, and then cool naturally to room temperature; (3) The magnetic black powder calcined in step (2) is ground and sieved, then washed with a 1.0 mol / L dilute hydrochloric acid solution, then washed with distilled water, and dried to obtain a graphitized carbon material.

2. The method for preparing a graphitized carbon material according to claim 1, characterized in that: In step (1), the mass ratio of D-(+)-xylose powder to transition metal salt powder is 4:

1.

3. The method for preparing a graphitized carbon material according to claim 1, characterized in that: In step (1), the transition metal salt powder is selected from one of FeCl3·6H2O, CoCl2·6H2O, and NiCl2·6H2O.

4. The method for preparing a graphitized carbon material according to claim 3, characterized in that: In step (1), the transition metal salt powder is FeCl3·6H2O.

5. The method for preparing a graphitized carbon material according to claim 1, characterized in that: In step (2), the inert gas is argon.

6. The graphitized carbon material prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the graphitized carbon material according to claim 6 in detecting aflatoxin B1 in vegetable oil, characterized in that: The graphitized carbon material FeO / Fe3O4 / HGC was used for magnetic solid phase extraction of aflatoxin B1 in vegetable oils, and the detection limit of aflatoxin B1 was as low as 2.0 pg·g in combination with high performance liquid chromatography-fluorescence detection. -1 .

Citation Information

Patent Citations

  • Fibers for decontamination of chemical and biological agents

    CN101680120A

  • Graphitized carbon material and preparation method thereof

    CN109368632A

  • Method for separating and enriching aflatoxin in vegetable oil

    CN112540132A

  • Preparation method and application of magnetic graphitized carbon black

    CN113041996A

  • Fe3O4 / FeO / C composite material, and preparation method and application thereof

    CN113328160A